APLIKASI PEMBELAJARAN PERALATAN TANJIDOR BERBASIS ANDROID - Yusuf Permadi; Nur Nafiiyah (Joutica, 2017)
Smartphone is the manifestation of the technological developments that can narrow space and time. Smartphone is not only used as a means of communication but as a means of entertainment for many kinds of applications that is presented by the developers. Android is an operating system that is widely used by several manufacturers of smartphones today. Application is a program which is designed to perform a function with specific goals and purposes. Tanjidor is the musical art of Betawi. Tanjidor did not come originally from Indonesia, but from Portuguese language in a word Tangedor which means “stringed musical instruments”. Tanjidor itselfis played in several musical instruments category, namely wind instruments (in particular instrument it is called as mouthpiece) like clarinet, trombone, tuba, saxophone, and trumpet. In addition, there is also wind instrument musical which played by hit it (in a particular type it is called a percussion), like snare drum, tenor drum, bass drum, cymbals and drums. Android-based Tanjidor equipment learning application is used as the entertainment media and also aims to preserve the Indonesian art heritage by inserting Tanjidor instruments in Android smartphon. Therefore, Tanjidor musical art does not disappear over the time.